Two sides to the evasion: The pirate bay and the interdependencies of evasive entrepreneurship - Niklas Elert; Magnus Henrekson; Joakim Lundblad (Research Institute of Industrial Economics (IFN), 2016)
Evasive entrepreneurs innovate by circumventing or disrupting existing formal institutional frameworks by evading them. Since such evasions rarely go unnoticed, they usually lead to responses from lawmakers and regulators. We introduce a conceptual model to illustrate and map the interdependence between evasive entrepreneurship and the regulatory response it provokes. We apply this framework to the case of the file sharing platform The Pirate Bay, a venture with a number of clearly innovative and evasive features. The platform was a radical, widely applied innovation that transformed the Internet landscape, yet its founders became convicted criminals because of it. Applying the evasive entrepreneurship framework to this case improves our understanding of the relationship between policymaking and entrepreneurship in the digital age, and is a first step towards exploring best responses for regulators facing evasive entrepreneurship.
Keywords: L5; M13; O31; P14; 330; Entrepreneurship; Innovation; Institutions; Regulation; Self-employment